2022
DOI: 10.1021/acsapm.1c01817
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Lignin-Containing Hydrogels with Self-Adhesion, Conductivity, UV Shielding, and Antioxidant Activity as Wearable Sensors

Abstract: Hydrogels have drawn intensive attention as emerging materials for various applications in wearable sensors, soft robotics, and implantable devices. However, fabricating hydrogels with UV-shielding and antioxidant properties still remains a challenge. Herein, we prepared biocompatible 3-allyloxy-2-hydroxypropyl-lignin/polyacrylic acid (AHP-lignin/PAA) hydrogels with self-adhesion, conductivity, UV shielding, and antioxidant activity as wearable sensors by the incorporation of lignin into PAA. The structure, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“… 12 14 Every year, 70 million tons of lignin are isolated as byproducts of the paper and pulp industry, and most of it is burned as a low-value fuel. 15 , 16 In addition to being biocompatible 17 19 and providing antioxidant activity, lignin also absorbs UV-light and thus allows to impart UV-barrier properties on food packaging materials. 19 22 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 14 Every year, 70 million tons of lignin are isolated as byproducts of the paper and pulp industry, and most of it is burned as a low-value fuel. 15 , 16 In addition to being biocompatible 17 19 and providing antioxidant activity, lignin also absorbs UV-light and thus allows to impart UV-barrier properties on food packaging materials. 19 22 …”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 In addition to being biocompatible 17 19 and providing antioxidant activity, lignin also absorbs UV-light and thus allows to impart UV-barrier properties on food packaging materials. 19 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin could improve the mechanical properties of plants and enhance their resistance to the surrounding environment . It has been widely used in low valued-added products including fillers, additives, binders, or surfactants. , Moreover, because of its specific structure, lignin shows several properties such as low cytotoxicity, UV-blocking property, antibacterial properties, , antioxidant properties, , and self-assembly capabilities …”
Section: Introductionmentioning
confidence: 99%
“…9 It has been widely used in low valued-added products including fillers, additives, binders, or surfactants. 10,11 Moreover, because of its specific structure, lignin shows several properties such as low cytotoxicity, 12 UV-blocking property, 13 antibacterial properties, 14,15 antioxidant properties, 16,17 and self-assembly capabilities. 18 As far as we know, only a few studies reported lignin-based NPs for cancer therapy.…”
Section: ■ Introductionmentioning
confidence: 99%